Full-Scale Load Testing of the Swift Rock Anchors (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Swift Anchor, designed and built by SCHOTTEL Marine Technologies (SMT), was created for challenging geotechnical and metocean environments to anchor floating marine energy systems. The system was originally designed for tidal energy sites, where rock seabeds are common due to scour from high speed flows. Additionally, high yield tidal energy sites have small slack water windows and so rapid installation is imperative to minimise time on site. By relying on a mechanical interlock between the anchor and the surrounding rock, the groutless self-drilling Swift Anchor utilises the load bearing capacity of rock. Thus, the technology represents a cost-efficient anchoring solution not only for tidal energy devices, but also for further floating marine energy systems in the field of wave and floating wind energy.In order to verify the Swift Anchor design, including installation efficiency and load bearing capacity, the anchors have undergone rigorous testing: onshore testing in quarry trials, and offshore in device applications. Most recently SMT have conducted a series of land trials in Dörth, Germany, to test the load holding limits, determined through numerical analyses. The anchor was designed to withstand the loads from a specific tidal energy device at a highly energetic tidal site, and so this defined the anchor sizing and minimum break load (MBL). Due to the variable water depth, flow speed, and load applied to the mooring lines (due to drag, thrust and wave loading) the anchor must operate within a wide range of load angles and limits. As the anchor is expanded into other markets, such as offshore wind and aquaculture, these regimes are further expanded.SMT have developed a novel test methodology including: static load testing, to prove the anchor’s specified load holding capacity; dynamic (or cyclic) load testing, to demonstrate fatigue loading; and test-to-failure to find the principal failure mechanism at the given site conditions. A unique test rig was designed and built which allows a test anchor to be installed in conjunction with another reaction anchor (so that loads are resisted between each anchor to reduce additional test equipment), and any load angle from 0 to 90° can be achieved for vertical, lateral, and inclined testing. The load holding envelope of the anchor can then be tested, as defined by given site conditions.This paper presents the details of the Swift Anchor, the test methodology, the test rig, and the geotechnical conditions of the test site. The initial load testing results will be presented to demonstrate that the novel test methodology and test rig represent a rigorous and efficient setup to de-risk critical infrastructure of floating marine energy systems